USE OF ICT BASED LIBRARY RESOURCE AND SERVICES IN CONSTITUENT FIRST GRADE COLLEGES AFFILIATED TO UNIVERSITY OF MYSORE: STUDY - Chikkamanju; Ambika; Ali, Hydar (International Journal of Research -GRANTHAALAYAH, 2016)
The study investigated the ICT based library and Information services in Constituent First Grade Colleges affiliated to University of Mysore .The present study demonstrates and elaborates the primary way to learn about ICTs, the purpose of using ICT enabled library services, to assess to what extent users are utilized ICT based library services and facilities, various aspects of Internet usage, favourite search engines, NLIST resources and services Suggestions have been given to make the service more beneficial in the library users. The aims were to examine impacts of ICT on motivation and related issues such as learning outcomes, behaviour, and attendance and to quantify any impacts where possible. The study also set out to consider the ways in which ICT can best be used by under graduate students to enhance motivational impacts for pupils, especially for those disaffected with traditional forms of learning. The present study aims to examine the ICT based library and Information services in Constituent First Grade Colleges affiliated to University of Mysore. The questionnaire method was adopted for the present study to collect the necessary data, keeping in view the objectives of the study. Total 236 questionnaires were distributed and 163 filled in questionnaires were collected back. The rate of response of 69.06 %. The collected data has been analysed using appropriate statistical techniques with SPSS such as chi-square test, mean and standard deviation for the analysis. The majority mean value of 3.28 SD being 1.66 I read e-Books of respondents110(67.48%) of students opine as ‘Excellent’, with a mean value of 1.59 and SD being 1.00. for Preferred search engine 20(12.26%) respondents use ‘Annual Reviews’ Use of N-List resources and Services From the analysis, it showed that our colleges should always embark on strategies towards adding more value to their ICT based library services. ICT based library services awareness program should be rendered to the graduate students at the very point of enrolment into the graduate studies for this will help the students to - wards understanding the need of utilizing the library properly and also appreciate technology more in their lives.